Self-Leadership of Nurses in Tertiary Hospitals, Yunnan Province, the People’s Republic of China - Liu , Jinyan; Chitpakdee , Bunpitcha; Akkadechanunt , Thitinut (Nursing Journal CMU, 2020)
Self-leadership is important in changing environments because it improves job performance, enhances group leadership and quality of care. The purposes of this descriptive comparative study were to explore the self-leadership of staff nurses and nurse managers and to compare the differences between these groups. The sample included 406 staff nurses and 316 nurse managers who were selected using multistage sampling technique from five tertiary hospitals in Yunnan Province, the People’s Republic of China. Research instruments included the Demographic Data Form and the Revised Self-Leadership Questionnaire (RSLQ). The Cronbach’s alpha coefficients of RSLQ for staff nurses and nurse managers were .97 and .91 respectively. Descriptive statistics, Mann-Whitney U test, and independent t-test were used for data analysis. Results were as follows: For staff nurses, the overall mean score of self-leadership (x̄ = 3.50, SD = .59) and its three dimensions including behavior-focused strategies (x̄ = 3.53, SD = .60), natural reward strategies (x̄ = 3.53, SD = .68), and constructive thought pattern strategies (x̄ = 3.45, SD = .65) were at a moderate level. For nurse managers, the overall mean score of self-leadership (x̄ = 4.02, SD = .45) and its three dimensions including behavior-focused strategies (x̄ = 4.03, SD = .46), natural reward strategies (x̄ = 4.01, SD = .54), and constructive thought pattern strategies (x̄ = 4.00, SD = .49) were at a high level. There were significant differences between staff nurses and nurse managers in overall mean score of self-leadership (t = -13.32, p < .01) and its dimensions including behavior-focused strategies (t = -12.77, p < .01), natural reward strategies (z = -9.90, p < .01), and constructive thought pattern strategies (t = -12.80, p < .01). These results provide baseline information for nurse administrators to enhance the self-leadership skills of nurses in order to improve job performance, group leadership, and quality of care.